Simple limbal epithelial transplantation (SLET): Review of indications, surgical technique, mechanism, outcomes, limitations, and impact - Shanbhag, Swapna S (Indian J Ophthalmol, 2019)
Simple limbal epithelial transplantation (SLET) is an innovative limbal stem cell transplantation technique that has gained increasing popularity over the last few years. Different groups from across the world have published the clinical results of SLET in large case series with varying types and severities of limbal stem cell deficiency (LSCD). This review attempts to place all the available knowledge on SLET together in one place for the benefit of not only cornea specialists and trainees but also for residents and general ophthalmologists. It follows a balanced approach of blending evidence with experience by providing an objective analysis of published results along with helpful insights from subject experts, starting from preoperative considerations including the role of newer imaging modalities to the technical aspects of the surgery itself and the management of possible complications. Original data and novel insights on allogeneic SLET for bilateral LSCD are included in the review to address the few remaining lacunae in the existing literature on this topic. This review intends to inform, educate, and empower all aspiring and practicing SLET surgeons to optimize their clinical outcomes and to have maximal positive impact on the lives of the individuals affected by unilateral or bilateral chronic LSCD.